Absorption, metabolism, and excretion of [14C]dersimelagon, an investigational oral selective melanocortin 1 receptor agonist, in preclinical species and healthy volunteers - Minoru Tsuda; Kei Ogawa; Tadashi Endou; Takahiro Goto; Yuko Ogasawara; Akihito Ogasawara (Wiley, 2023)
Abstract Dersimelagon (formerly MT‐7117) is a novel, orally administered nonpeptide small molecule selective agonist for melanocortin 1 receptor currently being investigated for the treatment of erythropoietic protoporphyria, X‐linked protoporphyria, and diffuse cutaneous systemic sclerosis (dcSSc). Findings of studies evaluating the absorption, distribution, metabolism, and excretion (ADME) of dersimelagon following a single dose of [14C]dersimelagon in healthy adult volunteers (N = 6) who participated in phase 1, single‐center, open‐label, mass balance study (NCT03503266), and in preclinical animal models are presented. Rapid absorption and elimination were observed following oral administration of [14C]dersimelagon in clinical and nonclinical studies, with a mean Tmax of 30 min in rats and 1.5 h in monkeys, and a median Tmax of 2 h in humans. In rats, there was a widespread distribution of [14C]dersimelagon‐related material, but little or no radioactivity was detected in the brain or fetal tissues. In humans, elimination of radioactivity in urine was negligible (excretion of radioactivity into the urine: 0.31% of dose), and the primary route of excretion was feces, with more than 90% of the radioactivity recovered through 5 days postdose. Based on these findings, dersimelagon is not retained in the human body. Findings from humans and animals suggest dersimelagon is extensively metabolized to the glucuronide in the liver, which is eliminated in bile, and hydrolyzed to unchanged dersimelagon in the gut. The results to date for this orally administered agent elucidate the ADME of dersimelagon in human and animal species and support its continued development for the treatment of photosensitive porphyrias and dcSSc.